2021
DOI: 10.4149/neo_2020_200803n811
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1 inhibition impairs the proliferation and migration of pancreatic stellate cells induced by pancreatic cancer cells

Abstract: Activated pancreatic stellate cells (PSCs) with an increased proliferation and migration ability are the partners in crime with pancreatic cancer cells. Acid-sensing ion channel 1 (ASIC1) is expressed in pancreatic cancer and PSCs, and especially, it mediates the activation of PSCs. However, whether ASIC1 is involved in pancreatic cancer cells-induced biological behavior re-educating of PSCs is unclear. In this study, the change of ASIC1 expression in PSCs and pancreatic cancer Panc-1 cells after indirect co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The current findings that ASIC1a contributes to hypoxia-induced PASMC proliferation and migration support a direct contribution of ASIC1a to vascular remodeling. These data corroborate several studies showing that ASIC1, expressed in a variety of cancers, plays a role in regulating multiple malignant processes including proliferation, migration, epithelial-mesenchymal transition, and cell cycle progression ( Kapoor et al, 2009 ; Rooj et al, 2012 ; Jin et al, 2015 ; Wu et al, 2017 ; Zhu et al, 2017 ; Chen et al, 2018 ; Ding et al, 2021 ; Zhu et al, 2021 ). Conversely, prevention of right ventricular hypertrophy following deletion of SM- Asic1a suggests cardiomyocyte remodeling in this mouse model of hypoxic pulmonary hypertension largely occurs due to the role of ASIC1a to increase pulmonary vascular resistance.…”
Section: Discussionsupporting
confidence: 90%
“…The current findings that ASIC1a contributes to hypoxia-induced PASMC proliferation and migration support a direct contribution of ASIC1a to vascular remodeling. These data corroborate several studies showing that ASIC1, expressed in a variety of cancers, plays a role in regulating multiple malignant processes including proliferation, migration, epithelial-mesenchymal transition, and cell cycle progression ( Kapoor et al, 2009 ; Rooj et al, 2012 ; Jin et al, 2015 ; Wu et al, 2017 ; Zhu et al, 2017 ; Chen et al, 2018 ; Ding et al, 2021 ; Zhu et al, 2021 ). Conversely, prevention of right ventricular hypertrophy following deletion of SM- Asic1a suggests cardiomyocyte remodeling in this mouse model of hypoxic pulmonary hypertension largely occurs due to the role of ASIC1a to increase pulmonary vascular resistance.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, activation of ASIC1 enhances calcium influx and initiates intracellular signaling to trigger downstream events, such as inflammation and cell death ( Wang and Xu, 2011 ; Zhang R. J. et al, 2020 ). ASIC1 plays crucial roles in physiological and pathophysiological processes, including vascular remodeling, cognitive function disorders, pancreatic cancer, and cerebral ischemic injury ( Detweiler et al, 2019 ; Zhou et al, 2019 ; Zhu et al, 2021 ). Recently, Ni et al (2018) reported that ASIC1 activation results in macrophage cell inflammatory response, which impedes ATP-binding cassette protein A1 (ABCA1)-mediated cholesterol efflux from the cells.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the activation of ERK via ASIC1a (downstream ASIC1a activation) has been analyzed in different pathological conditions (Chen et al, 2016;Sun et al, 2018;Zhu et al, 2020Zhu et al, , 2021. In addition, this pathway has also been linked to inflammation (Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%